What Are the Ethical Issues in Treating a Patient With Bilateral Leg Gangrene Incapable of Consenting to Amputation Secondary to Psychiatric Illness?. Issue 12 (December 2015) - Taylor, Michel; McKay, Douglas; Eid, Moustafa; Schuklenk, Udo; Pichora, David
Abstract: Background: Bilateral and simultaneous lower extremity amputations unrelated to diabetes and peripheral vascular disease are uncommon, although they may be necessary in patients with severe blast injuries. Such amputations, however, usually are performed in patients who are able to understand and consent to the treatment. Case Description: We present the case of a 29‐year‐old woman who experienced drug‐induced psychosis and underwent substantial hypothermic injuries; most notably, irreversible frostbite injuries to both lower extremities, leading to dry and mummified gangrene. As a result of her psychiatric illness, fluctuating catatonic state, and lack of insight into her clinical condition, she was deemed incapable of making decisions regarding her medical care and her mother was made substitute decision maker. The orthopaedic service was consulted regarding possible surgical treatment of her gangrenous feet that were stable and aseptic after limb preservation efforts (including hyperbaric oxygen) had been tried without success. They recommended close clinical monitoring and continued psychiatric treatment. The family, including the substitute decision maker, citing the patient's best interest, rejected the recommendations of the surgical team and demanded immediate surgical transtibial amputation of both lower legs. Literature Review: To our knowledge, such a unique case has not been reported. Clinical Relevance: We examined the decision‐making process, the difficulties of caring for such a patient, and the ethical issues that arose.